Effects of ambient particulate exposure on blood lipid levels in hypertension inpatients - Gao, Yanfang; Li, Chenwei; Huang, Lei; Huang, Kun; Guo, Miao; Zhou, Xingye; Zhang, Xiaokang (Frontiers in Public Health, 2023)
With modernization development, multiple studies of atmospheric particulate matter exposure conducted in China have confirmed adverse cardiovascular health effects. However, there are few studies on the effect of particulate matter on blood lipid levels in patients with cardiovascular disease, especially in southern China. The purpose of this study was to investigate the effects of short- and long-term exposure to ambient particulate matter on the levels of blood lipid markers in hypertension inpatients. Data on admission lipid index testing for hypertension inpatients were extracted from the hospital's big data center, and air pollution and meteorology data were acquired from the China urban air quality real time release platform and climatic data center, with data integrated according to patient admission dates. The total hypertension inpatients were divided into those with and without arteriosclerosis disease. A semi-parametric generalized additive model (GAM) was established to calculate the association between ambient particulate matter and blood lipid markers in hypertension inpatients with different exposure time in one year. Long-term exposure to particulate matter was associated with increased Lp(a) in three kinds of people, and with increased TC and decreased HDL-C in total hypertension and hypertension with arteriosclerosis. Particulate matter was associated with increased HDL-C for hypertension inpatients without arteriosclerosis, at the time of exposure in the present study. It is speculated that hypertension inpatients without arteriosclerosis has better statement than hypertension inpatients with arteriosclerosison human lipid metabolism. Long-term exposure to ambient particulate matter is associated with adverse lipid profile changes in hypertension inpatients, especially those with arteriosclerosis. Ambient particulate matter may increase the risk of arteriosclerotic events in hypertensive patients.